Importance of Imaging in Congenital Unilateral Vocal Fold Paralysis: A Case of Neck Neuroblastoma Presenting with Unilateral Vocal Fold Paralysis - Yeo, W. X.; Chan, C. Y.; Tan, K. K. H. (Case Reports in Otolaryngology, 2021)
Congenital vocal fold paralysis (VFP) is an important cause of respiratory compromise in infants. It can either be unilateral or bilateral, while imaging is routinely performed for bilateral VFP to evaluate for potential neurological causes, and such a practice may not be routine for unilateral VFP. While many of the unilateral VFP cases are idiopathic, the cause may occasionally be more sinister in nature, such as tumors. Therefore, unless an obvious cause of unilateral VFP is present (such as cardiac surgery or birth trauma), routine imaging of the brain, neck, and mediastinum should be performed for congenital unilateral VFP. We describe a rare case of a cervical neuroblastoma presenting with unilateral VFP that was detected only on imaging, thus highlighting its value and importance.